The cell type‐specific ER membrane protein UGS148 is not essential in mice. (23rd December 2021) - Takahashi, Osamu; Tanahashi, Mayuko; Yokoi, Saori; Kaneko, Mari; Yanaka, Kaori; Nakagawa, Shinichi; Maita, Hiroshi
Abstract: Genomes of higher eukaryotes encode many uncharacterized proteins, and the functions of these proteins cannot be predicted from the primary sequences due to a lack of conserved functional domains. In this study, we focused on a poorly characterized protein UGS148 that is highly expressed in a specialized cell type called tanycytes that line the ventral wall of the third ventricle in the hypothalamus. Immunostaining of UGS148 revealed the fine morphology of tanycytes with highly branched apical ER membranes. Immunoprecipitation revealed that UGS148 associated with mitochondrial ATPase at least in vitro, and ER and mitochondrial signals occasionally overlapped in tanycytes. Mutant mice lacking UGS148 did not exhibit overt phenotypes, suggesting that UGS148 was not essential in mice reared under normal laboratory conditions. We also found that RNA probes that were predicted to uniquely detect UGS148 mRNA cross‐reacted with uncharacterized RNAs, highlighting the importance of experimental validation of the specificity of probes during the hybridization‐based study of RNA localization. Abstract : In this study, we have investigated physiological function of poorly characterized ER membrane protein UGS148. We also found that RNA probes that were predicted to uniquely detect UGS148 mRNA cross‐reacted with uncharacterized RNAs, highlighting the importance of experimental validation of the specificity of probes during the hybridization‐based study of RNA localization.